2013
DOI: 10.1111/joa.12016
|View full text |Cite
|
Sign up to set email alerts
|

Stages and duration of the seminiferous epithelium cycle in the bat Sturnira lilium

Abstract: Knowledge of the stages that compose the seminiferous epithelium cycle (SEC) and determination of the duration of spermatogenic processes are fundamental for the accurate quantification of the dynamics of spermatogenesis. The aim of this study was to characterize the stages that compose the SEC of the bat Sturnira lilium, including evaluation of the average frequency of each of these stages throughout the year and calculation of the duration of the spermatogenic process. An ultrastructural characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
(87 reference statements)
4
14
0
2
Order By: Relevance
“…The presence of eight stages of the SEC, based on tubular morphology (Clermont, ), described for yellowish myotis (present study) has been similarly described for the Neotropical phyllostomid bats Artibeus lituratus , Artibeus planirostris , Carollia perspicillata , Platyrrhinus lineatus and Sturnira lilium (Beguelini et al., ; Oliveira et al., ; Morais et al., ), but not for the vespertilionid M. nigricans in which different cell associations were registered in seminiferous tubule cross‐sections (Beguelini et al., ).…”
Section: Discussionsupporting
confidence: 75%
“…The presence of eight stages of the SEC, based on tubular morphology (Clermont, ), described for yellowish myotis (present study) has been similarly described for the Neotropical phyllostomid bats Artibeus lituratus , Artibeus planirostris , Carollia perspicillata , Platyrrhinus lineatus and Sturnira lilium (Beguelini et al., ; Oliveira et al., ; Morais et al., ), but not for the vespertilionid M. nigricans in which different cell associations were registered in seminiferous tubule cross‐sections (Beguelini et al., ).…”
Section: Discussionsupporting
confidence: 75%
“…One exception is the vespertilionid Myotis nigricans, in which different cell associations occur in cross-sections of the seminiferous tubule (BEGUELINI et al 2009). The species-constant relative frequencies of stages of the SEC (HESS & FRANÇA 2007) were confirmed by our study and, similarly to the results of a study on Sturnira lilium (E. Geoffroy, 1810) (MORAIS et al 2013), no differences were detected between the rainy and the dry seasons. The smaller accumulated frequency of premeiotic stages with respect to post-meiotic stages, obtained in the present study, was similar to the results of BEGUELINI (2009).…”
Section: Discussionsupporting
confidence: 78%
“…The eight stages of the SEC previously described for this species (BEGUELINI et al 2009) have been confirmed in the present study. In general, the cellular composition of these stages is similar to that of other mammals, including other Neotropical phyllostomids (BEGUELINI et al 2009, OLIVEIRA et al 2009, MORAIS et al 2013. One exception is the vespertilionid Myotis nigricans, in which different cell associations occur in cross-sections of the seminiferous tubule (BEGUELINI et al 2009).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In humans, a 3-day period of sexual abstinence provides optimal sperm quality (Levitas et al, 2005;Marshburn et al, 2014). Moreover, such a short abstinence period may not allow modifications of the sperm structure to take place (Morais et al, 2013). Under the assumptions that sneaker males copulate less frequently than harem males, and that 3 days of sexual abstinence is common for them, we predicted that sneaker males should not show changes in the SOD and MDA ratios, blood GSH ratio or sperm quality.…”
Section: Introductionmentioning
confidence: 99%